Process of Adopting Information and Communication Technology (ICT) Innovations in Vocational Learning for Autism Spectrum Disorder (ASD) Students during the Covid-19 Pandemic - Firmansyah, Dwi; Lubis, Djuara P.; Muljono, Pudji; Purnaningsih, Ninuk (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Online learning demands specific teacher preparation, particularly in the effective utilization of Information and Communication Technology (ICT) innovations tailored to the unique needs and capabilities of students with autism spectrum disorder (ASD). This study focused on the ICT innovations adopted by educators at the London School Beyond Academy (LSBA), a vocational school catering to autistic students in Jakarta, during the COVID-19 pandemic. A total of 8 main informants who are educators were selected by snowbowling sampling. Data collection involved multiple methods, including in-depth interviews, observations, and literature reviews. Documentation included archiving interview recordings, interview transcripts, and observation notes. The data analysis technique was carried out by adopting the conceptual framework of